2005
DOI: 10.1111/j.1365-2222.2005.02319.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between bronchodilating response to short‐acting β‐agonist and non‐synonymous single‐nucleotide polymorphisms of β2‐adrenoceptor gene

Abstract: Non-synonymous SNPs of ADRB2 at codons 16 and 27 is significantly associated with bronchodilating response to inhaled short acting beta-agonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 20 publications
4
25
1
Order By: Relevance
“…Furthermore, in a study that demonstrated an association between asthma and ADAM33 in multiple populations, different SNPs were associated with asthma in each population [24]. Likewise, the Arg16Gly polymorphism in the beta 2 -adrenergic receptor (ADRB2) has been associated with bronchodilator response to albuterol in three mixed U.S. populations, one Korean population and one Puerto Rican population [31][32][33][34][35], but not in Mexican or African American populations [32,36].…”
Section: Genetic Risk Factors For Asthmamentioning
confidence: 99%
“…Furthermore, in a study that demonstrated an association between asthma and ADAM33 in multiple populations, different SNPs were associated with asthma in each population [24]. Likewise, the Arg16Gly polymorphism in the beta 2 -adrenergic receptor (ADRB2) has been associated with bronchodilator response to albuterol in three mixed U.S. populations, one Korean population and one Puerto Rican population [31][32][33][34][35], but not in Mexican or African American populations [32,36].…”
Section: Genetic Risk Factors For Asthmamentioning
confidence: 99%
“…In a previous study, increased adrenoceptor downregulation was found to be related to the ADRB2 46A>G polymorphism [33]. However, previous studies failed to find significant associations between the Gln27Glu or Arg16Gly ADRB2 polymorphisms and total serum IgE levels in the Korean population [15,34,35]. In terms of specific IgE sensitization, Llanes et al [36] demonstrated no significant association between genetic variations of ADRB2 46A>G polymorphisms and the risk of olive pollen sensitization and asthma.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, there is evolving evidence that genetic variation in the β 2 -receptor influences bronchodilator response to both short-and long-acting β 2 -agonist drugs. 27 Patients with specific β 2 -adrenoreceptors appear to respond less favourably to traditional β 2 -agonists; and may also represent a group that may benefit from alternative bronchodilators.…”
Section: Discussionmentioning
confidence: 99%